Password systems: Design and implementation. (October 2015) - Dini, Gianluca; Lopriore, Lanfranco
Graphical abstract: Highlights: A significant protection problem is to specify the access privileges held by each active subject on the protected objects. We associate a password system with each object, featuring a password for each access privilege. Access privileges are partitioned into privilege levels, for distribution and revocation. Password systems are implemented as hierarchical bidimensional one-way chains. Abstract: Critical infrastructures require protection systems that are both flexible and efficient. Flexibility is essential to capture the multi-organizational and state-based nature of these systems, efficiency is necessary to cope with limitations of hardware resources. To meet these requirements, we consider a classical protection environment featuring subjects that attempt to access the protected objects. We approach the problem of specifying the access privileges held by each subject. Our protection model associates a password system with each object; the password system features a password for each access privilege defined for this object. A subject can access the object if it holds a key matching one of the passwords in the password system, and the access privilege corresponding to this password permits to accomplish the access. Password systems are implemented as hierarchical bidimensional one-way chains. Trade-offs are possible between the memory requirements for storage of a password system and the processing time necessary to validate a key.